PVM/MA-shelled selol nanocapsules promote cell cycle arrest in A549 lung adenocarcinoma cells - Souza, Ludmilla Regina de (2014)
Background: Selol is an oily mixture of selenitetriacylglycerides that was obtained as a semi-synthetic compound containing selenite. Selol is effective against cancerous cells and less toxic to normal cells compared with inorganic forms of selenite. However, Selol’s hydrophobicity hinders its administration in vivo. Therefore, the present study aimed to produce a formulation of Selol nanocapsules (SPN) and to test its effectiveness against pulmonary adenocarcinoma cells (A549). Results: Nanocapsules were produced through an interfacial nanoprecipitation method. The polymer shell was composed of poly(methyl vinyl ether-co-maleic anhydride) (PVM/MA) copolymer. The obtained nanocapsules were monodisperse and stable. Both free Selol (S) and SPN reduced the viability of A549 cells, whereas S induced a greater reduction in non-tumor cell viability than SPN. The suppressor effect of SPN was primarily associated to the G2/M arrest of the cell cycle, as was corroborated by the down-regulations of the CCNB1 and CDC25C genes. Apoptosis and necrosis were induced by Selol in a discrete percentage of A549 cells. SPN also increased the production of reactive oxygen species, leading to oxidative cellular damage and to the overexpression of the GPX1, CYP1A1, BAX and BCL2 genes. Conclusions: This study presents a stable formulation of PVM/MA-shelled Selol nanocapsules and provides the first demonstration that Selol promotes G2/M arrest in cancerous cells.